Comparative study on effect of different embryo culture media on in vitro blastocyst production in goats - GOEL, PUJA; GOEL, A K; BHATIA, A K; KHARCHE, S D (The Indian Journal of Animal Sciences, 2016)
The present study was aimed to assess the efficacy of different culture media for blastocyst development. Oocytes (2,539) from 1,059 ovaries recovered by follicle puncture technique were utilized for present investigation. In experiment 1, effect of different embryo culture media (Gr. 1; mKSOMaa; Gr. 2; TCM-199+OEC; Gr. 3; mSOFaa and Gr. 4; mCR2aa) and in experiment 2, effect of sequential embryo culture medium, Gr. 1: mKSOMaa containing 5% FBS (1–3 days) and 10% FBS (4–10 days); Gr. 2: 0.8% BSA (1–3 days) and continuous embryo culture medium, 10% FBS (4–10 days); Gr. 3: 0.8% BSA (1–10 days) and Gr. 4: 10% FBS (1–10 days) on in vitro blastocyst development potential was evaluated. Significant higher (P<0.05) blastocyst production rate was observed in TCM– 199 co-culture with OEC and mKSOMaa medium compared to mSOFaa embryo culture medium. Similarly, significantly higher morula production rate was observed in mKSOMaa medium compared to mSOFaa and mCR2aa medium. However, numerically higher number of embryos cleaved in mSOFaa medium compared to TCM-199 co- culture with OEC. Results indicated that embryos cultured in mKSOMaa, TCM-199+OEC and mCR2aa embryo development media are equally effective in supporting pre-implantation development.While considering the risk factor associated with OEC co-culture, mKSOMaa is proved to be efficient medium for obtaining higher in vitro embryo development rate. In experiment 2, significantly higher morula and blastocyst formation was observed in sequential embryo culture medium compared to BSA supplemented continuous embryo culture medium. Further, the present findings indicated that the use of mKSOMaa+0.8% BSA or 5% FBS for first 3 days of embryo culture resulted in increased rate of blastocyst stage embryos, if initial 3 days of culture in mKSOMaa+0.8% BSA was followed by culture in mKSOMaa containing 10% FBS. However, no significant difference was observed in sequential embryo culture medium and continuous embryo culture medium supplemented with 10% FBS.